From Schengen to Prüm: Deeper integration through enhanced cooperation or signs of fragmentation in the EU? - Daniela Kietz; Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2006)
The convention on stepping up cross border cooperation, particularly in combating terrorism, cross border crime and illegal migration, initiated by the Germans and signed in Prüm (Germany) on May 27, 2005, represents a new element in the fragmented landscape of European Justice and Home Affairs. The signatories of the so called Prüm Treaty are Belgium, Germany, Spain, France, Luxembourg, the Netherlands and Austria. Presently, the treaty is going through the ratification process in each of these countries. The treaty bears the marks of the Schengen integration process and thus creates questions regarding its role in the future development of European Justice and Home Affairs policy. In particular, how will the democratic oversight of such deepened integration among a small circle of EU member states be ensured? And above all, is this treaty compatible with the European Union's goal of establishing an EU-wide area of freedom, security and justice as set out prominently in the European Treaties? (SWP-Comments / SWP)
Keywords: 320